NEW PATHWAYS AND PARTNERSHIPS TO SCHOOL LEADERSHIP - Leiker, Virginia; Hutto, Nora; Campos, Theresa (European Scientific Journal, ESJ, 2014)
This paper describes an innovative partnership between the largest school district in the State of Texas, Houston Independent School District, and the Schools of Business and Education at the University of St. Thomas. The program includes a 48-hour master’s degree, resulting in a Master’s of Business Administration with principal certification. Through this university–school district collaboration, students are taught to apply principles of business including finance and leadership to diverse, inner-city school communities